The Effectiveness of Village Head Performance in Public Service According to Law Number 6 Of 2014 On Village Development from The Perspective of Fiqh Siyasah - Abd Mukhsin; Mitra Perdana (Journal Equity of Law and Governance, 2025)
This research aims to analyze the effectiveness of the village head's performance in public services according to Law Number 6 of 2014 concerning Villages, as well as to examine the perspective of fiqh siyasah in the implementation of these tasks. The method used is a qualitative approach, with data collection through in-depth interviews, observations, and studies in Kinangkung village, Sibolangit District, Deli Serdang Regency. The research results show that the effectiveness of the village head's performance is influenced by factors such as transparency, accountability, and community participation. The principles of fiqh siyasah, such as justice, deliberation, and public welfare, provide an important ethical foundation in decision-making. This research recommends enhancing the capacity of village heads through training, as well as strengthening community participation in the village development process, to achieve more effective and equitable public services. This research uses a qualitative approach with descriptive analysis, integrating the principles of fiqh siyasah related to governance and leadership in Islam. Fiqh siyasah focuses on the principles of justice, accountability, and community welfare in governance. This research evaluates the performance of village heads in the context of implementing the Village Development Law, including the planning, execution, and supervision of village development policies. The research results show that the effectiveness of the village head's performance is influenced by community satisfaction, service speed, transparency, and accountability. The perspective of fiqh siyasah provides an ethical framework and leadership principles that can enhance the quality of public service and the accountability of village heads.